Stem Cell-Specific Mechanisms Ensure Genomic Fidelity within HSCs and upon Aging of HSCs - Bettina M. Moehrle; Kalpana Nattamai; Andreas Brown; Maria C. Florian; Marnie Ryan; Mona Vogel; Corinna Bliederhaeuser; Karin Soller; Daniel R. Prows; Amir Abdollahi; David Schleimer; Dagmar Walter; et al. (Cell Reports, 2015)
Whether aged hematopoietic stem and progenitor cells (HSPCs) have impaired DNA damage repair is controversial. Using a combination of DNA mutation indicator assays, we observe a 2- to 3-fold increase in the number of DNA mutations in the hematopoietic system upon aging. Young and aged hematopoietic stem cells (HSCs) and hematopoietic progenitor cells (HPCs) do not show an increase in mutation upon irradiation-induced DNA damage repair, and young and aged HSPCs respond very similarly to DNA damage with respect to cell-cycle checkpoint activation and apoptosis. Both young and aged HSPCs show impaired activation of the DNA-damage-induced G1-S checkpoint. Induction of chronic DNA double-strand breaks by zinc-finger nucleases suggests that HSPCs undergo apoptosis rather than faulty repair. These data reveal a protective mechanism in both the young and aged hematopoietic system against accumulation of mutations in response to DNA damage.